Modulation of tactile duration judgments by emotional pictures - Shi, Zhuanghua; Jia, Lina; Mueller, Hermann J. (Frontiers in Integrative Neuroscience, 2012)
Judging the duration of emotional stimuli is known to be influenced by their valence and arousal values. However, whether and how perceiving emotion in one modality affects time perception in another modality is still unclear. To investigate this, we compared the influence of different types of emotional pictures—a picture of threat, disgust, or a neutral picture presented at the start of a trial—on temporal bisection judgments of the duration of a subsequently presented vibrotactile stimulus. We found an overestimation of tactile duration following exposure to pictures of threat, but not pictures of disgust (even though these scored equally high on arousal), in a short-range temporal bisection task (range 300/900 ms). Follow-up experiments revealed that this duration lengthening effect was abolished when the range to be bisected was increased (1000/1900 ms). However, duration overestimation was maintained in the short-range bisection task regardless of whether the interval between the visual and tactile events was short or long. This pattern is inconsistent with a general arousal interpretation of duration distortion and suggests that crossmodal linkages in the processing of emotions and emotional regulation are two main factors underlying the manifestation of crossmodal duration modulation.